Isolation and structure elucidation of unexpected in‐process impurities during tetrazole ring formation of an investigational drug substance. (3rd February 2016) - Silva Elipe, Maria Victoria; Yoo, Chul; Xia, Fang; Simiens, Jason; Crossley, Kevin; Huckins, John R.; Guo, Hong‐Xun; Tedrow, Jason; Wong‐Moon, Kirby
Abstract: During the formation of a tetrazole ring on an investigational drug, two in‐process impurities were detected and analyzed by LC–MS, which suggested that both impurities were drug‐related with the same mass‐to‐charge ratio. To understand and control their formation, both impurities were isolated from the mother liquor of the reaction using a multi‐step isolation procedure to obtain a sufficient amount for high‐resolution mass spectrometry (HRMS) and NMR structural analysis. HRMS suggested a protonated mass of 577.32 Da for both impurities; however, MS fragmentation patterns provided limited information on their structures. NMR analysis indicated the presence on an additional NH functional group in both isolates with similar spatial and bond correlations to one of the dimethylcarbamoyl moieties and the corresponding aromatic ring. A phenyldimethylcarbamoylamino moiety was supported by the NMR and HRMS data and could be explained based on the 'Schmidt‐like' reaction mechanism, which was an unexpected reaction pathway. Because the reaction conditions were fixed because of safety concerns, the crystallization protocol was redesigned to reduce the levels of these impurities significantly. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Two in‐process impurities of identical protonated mass of ca. 577.32 Da and fragmentation patterns were observed during the formation of the tetrazole ring in an intermediate of an investigational drug. A multi‐step isolation procedure from the mother liquor of the reaction was performed for structural elucidation. NMR indicated the presence of an additional NH functional group in both isolates with similar spatial and bond correlations. The unexpected formation of a benzodimethylcarbamoylamino moiety appears to be resulting from a 'Schmidt‐like' reaction.